Vernacular Architecture, places and landscapes in the cinematographic universe of António Reis and Margarida Cordeiro (Simbiótica. Revista Eletrônica, 2022)
This article is placed in the fields of Arts and Humanities, crossing subjects from the scientific areas of Architecture and Cinema, being a reflection on the contributions and collaboratios of architects from the School of Fine Arts of Oporto in distinguishing inhabited spaces, places and landscapes of the cinematographic universe by António Reis & Margarida Cordeiro. In the first part, deepens the connections between António Reis with students and teachers of the School of Fine Arts of Oporto, who will have stimulated the cinematographic interest in the region of Trás-os-Montes, and in the second part analyzes and interprets, from two simultaneous and converging perspectives, the same cinematographic objects: “Trás-os-Montes”, 1976 and “Ana”, 1982.Keywords: António Reis and Margarida Cordeiro; Architecture and Cinema; New Cinema; Fine Arts of Oporto; Trás-os-Montes Region; Inhabited spaces; Landscape.